European policy in the coalition agreements of political parties in Germany – continuation or change after the 2021 elections? - Bielawska, Agnieszka (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2024)
The article aims to provide an overview of the European policies of two successive German government coalitions: the CDU, CSU and SPD, as well as the SPD, Alliance 90/die Grünen and FDP, as defined in their respective 2018 and 2021 coalition agreements. To this end, a comparative method was used in the article, making it possible to present the views of the CDU/ CSU and SPD coalition and the SPD, B90/die Grünen and FDP on European policy, and point out the differences and similarities between them. Content analysis was also employed to examine and interpret the government coalition agreements of 2018 and 2021, which were the main research material. The article was divided into several sections corresponding to the content of the two documents and to the research questions posed in their analysis. The study made it possible to verify the hypothesis that the European policies presented in the March 2018 and December 2021 coalition agreements are similar, which means that the Olaf Scholz government continues to deepen integration and expand the European Union. Artykuł ma na celu przybliżenie polityki europejskiej dwóch następujących po sobie niemieckich koalicji rządowych: CDU, CSU i SPD oraz SPD, Sojuszu 90/Zielonych i FDP, która określona została w zawartych przez partie umowach koalicyjnych z 2018 i 2021 r. W związku z powyższym, podczas pisania artykułu użyta została metoda porównawcza, dzięki której przybliżone zostały poglądy koalicji CDU/CSU i SPD oraz SPD, B90/die Grünen i FDP dotyczące polityki europejskiej oraz wskazane zostały różnice i podobieństwa owych poglądów. Wykorzystana została również analiza treści, która umożliwiła zbadanie i zinterpretowanie rządowych umów koalicyjnych z lat 2018 i 2021, które były głównym materiałem badawczym. Artykuł podzielony został na kilka części odpowiadających zawartości obu dokumentów oraz postawionym w ramach ich analizy pytaniom badawczym. Rezultatem badań było zweryfikowanie hipotezy, że polityka europejska zaprezentowana w umowach koalicyjnych z marca 2018 i grudnia 2021 r. jest zbliżona, co oznacza, że rząd Olafa Scholza kontynuuje pogłębianie integracji i rozszerzanie Unii Europejskiej.
Polityka europejska w umowach koalicyjnych niemieckich partii politycznych – kontynuacja czy zmiana po wyborach w 2021 roku?
Keywords: German European policy; German political parties; deepening integration; EU enlargement; niemiecka polityka europejska; niemieckie partie; pogłębianie integracji; rozszerzanie UE